Pengaruh Tekanan Ketaatan, Pengetahuan, Dan Pengalaman Auditor Terhadap Audit Judgment - Lambok Tampubolon (Universitas Trunojoyo Madura, 2018)
This research is quantitative research. The data used in this study is primary data by distributing questionnaires to public accounting firms domiciled in DKI Jakarta. The population in this study were auditors who worked in the Public Accounting Office. Questionnaires were distributed as many as 130 questionnaires and data that could be processed as many as 100 questionnaires. Data is processed using the help of SPSS 23. The purpose of this study is to examine the effect of auditor compliance, knowledge and experience on audit judgment. From a sample of 17 public accounting firms in DKI Jakarta, this study shows that: (1) obedience pressure has a significant positive effect on audit judgment, (2) knowledge has a significant positive effect on judgment audits, and (3) auditor experience has no effect on judgment audit.